Adaptive Leadership and Digital Transformation in Maritime Vocational Curriculum Development - Naomi Louhenapessy; Irfan Faozun; Marihot Simanjuntak (PT. Global Research Collaboration, 2026)
Maritime vocational education is under growing pressure to equip graduates with competencies that extend beyond operational seamanship into the domains of digital transformation, sustainability governance, and quantitative decision-making. Yet existing curricula have been slow to integrate these dimensions systematically, partly because the institutional leadership capacity required to drive such reform remains underdeveloped. This study examines how maritime institutional leaders (including program coordinators, department heads, and maritime instructors) which enact adaptive leadership in the context of curriculum reform to facilitate the embedding of digital transformation competencies within maritime vocational education. Employing a qualitative-dominant mixed-methods exploratory design, data were collected through semi-structured interviews, curriculum document analysis, and stakeholder group discussions with maritime industry experts, vocational lecturers, and recent graduates (n = 52). Thematic analysis identified three overarching themes: institutional adaptive capacity under digital disruption, the pedagogy-industry competency gap, and sustainability governance as emergent curriculum priority. Supplementary Likert-scale validation yielded overall mean scores ranging from 4.51 to 4.61 across four competency domains, corroborating qualitative patterns. Findings demonstrate that adaptive leadership functions not merely as one competency among many but as the organizational mediator that determines whether digital transformation initiatives succeed within maritime institutional environments. The study offers the first empirically grounded, context-specific model positioning adaptive leadership as a structural prerequisite for maritime vocational curriculum reform, with direct implications for institutional governance, accreditation policy, and faculty development